Pertemanan Lintas Iman: Kajian Toleransi Beragama dalam Perspektif Fenomenologi dan Al-Hadis di Sermani Kota Makassar - Fadhlina Arief Wangsa; Andi Nirwana (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
Conflict often emerges when friendships in a diverse society like Indonesia are founded upon differing ideological foundations. These tensions are typically rooted in variations in belief systems and interpersonal interactions among individuals or groups. Such discord can disrupt social harmony, particularly within familial contexts, and can subsequently impact political, economic, and societal stability. This article seeks to describe, illustrate, and analyze the practices and procedures employed in resolving enduring conflicts between Muslims and Christians in Makassar City. Employing a qualitative methodology grounded in phenomenology and lived experience, the researcher conducted direct observations and in-depth interviews. These methods were further supported by an exploration of hadiths pertaining to interfaith harmony. The findings indicate that Muslims and Christians in the Sermani area maintain strong and positive relationships, which extend beyond routine interactions into collaborative social activities, including mutual aid and conflict resolution. The study emphasizes that Islamic teachings, particularly those conveyed through hadith, encourage Muslims to cultivate good relations with all people, including Christians. To mitigate negative perceptions of religion, it is recommended that the government increase support for Islamic education, with a particular focus on peacebuilding and addressing issues of religious persecution.